2018
DOI: 10.1200/jco.2017.76.8390
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Based First-Line Treatment of Elderly Patients With Advanced Non–Small-Cell Lung Cancer: Joint Analysis of MILES-3 and MILES-4 Phase III Trials

Abstract: Purpose To test the efficacy of adding cisplatin to first-line treatment for elderly patients with advanced non-small-cell lung cancer (NSCLC) within a combined analysis of two parallel phase III trials, MILES-3 and MILES-4. Patients and Methods Patients with advanced NSCLC who were older than age 70 years with Eastern Cooperative Oncology Group performance status 0 to 1 were randomly assigned to gemcitabine or pemetrexed, without or with cisplatin. In each trial, 382 events were required to detect a hazard ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Cisplatin-based chemotherapy is considered as the first-line treatment for NSCLC. 13 , 14 Despite cisplatin-based chemotherapy is effective, development of drug resistance is a usual incidence during the course of cisplatin treatment. 15 , 16 It is urgent for us to explore useful approaches to reverse the resistance against cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin-based chemotherapy is considered as the first-line treatment for NSCLC. 13 , 14 Despite cisplatin-based chemotherapy is effective, development of drug resistance is a usual incidence during the course of cisplatin treatment. 15 , 16 It is urgent for us to explore useful approaches to reverse the resistance against cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Nowadays, cisplatin-based chemotherapy is still used as the first-line treatment for NSCLC. 13 , 14 However, virtually all of the NSCLC cells eventually become resistant to cisplatin because of the long-term use of it. 15 , 16 Novel approaches are required to overcome the resistance of cisplatin in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Patients treated with cisplatin were more predisposed to both haematologic and non--haematologic toxicity. 8 The Japanese trial JCOG0803/WJOG4307L also demonstrated that the combination ChT with cisplatin was not associated with superior overall survival. This trial compared tri -weekly docetaxel as monotherapy to a combination therapy (weekly cisplatin plus docetaxel) in stage III or IV NSCLC with ≥ 70 years with ECOG performance status 0 -1.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with advanced NSCLC aged >70 years or with PS 2, single-agent chemotherapy with a third-generation agent remains the standard of care, while a platinumbased doublet chemotherapy (usually with carboplatin) is recommended only in selected cases (Table 4). [81][82][83][84][85][86][87][88][89]…”
Section: Strong For Lowmentioning
confidence: 99%